Pengaruh Disiplin Kerja dan Motivasi Kerja Terhadap Kinerja Karyawan Dengan Kepuasan Kerja Sebagai Variabel Intervening pada Karyawan PT Karya Sidorukun Santosa - Cahyanisyam, Sherin Novia; Baskoro, Heru (VISA: Journal of Vision and Ideas, 2024)
This research aims to analyze the influence of work discipline and work motivation on employee performance with job satisfaction as an intervening variable at PT Karya Sidorukun Santosa. The method used in this research is a quantitative approach with data obtained through distributing questionnaires which are then tested using the Partial Least Square (PLS) method with SmartPLS 4.0 software. The sampling technique used the saturated sampling method where the total sample in this study was all employees of PT Karya Sidorukun Santosa. The results of data analysis show that work discipline has a positive effect on employee performance, work motivation has no effect on employee performance, work discipline has no effect on employee job satisfaction, work motivation has a positive effect on job satisfaction, while job satisfaction has no effect on employee performance.